The relationship between learning styles and English language achievement and gender among diploma students at a public university in Malaysia / Dr. Nor Ashikin Ab Manan, Johana Yusof and Noraziah Azizan - Ab Manan, Nor Ashikin; Yusof, Johana; Azizan, Noraziah (Universiti Teknologi MARA, Kedah, 2024)
The objectives of the study were to identify the preferred learning styles of diploma level students who are learners of English as a second language, in an environment where English is used as the medium of instruction, to determine whether there is a significant relationship between learning styles and English language achievement, and to establish whether there is a relationship between learning styles and gender. The participants for the study were 257 diploma level students from a public university in Malaysia. The research instrument chosen for the study was VAK Learning Style Inventory developed by Victoria Chislett and Alan Chapman (2005). The data collected were analysed descriptively using Microsoft Excel to determine the participants’ learning style preferences. A non-parametric Chi-square test of independence was conducted to establish whether there is a relationship between the two sets of categorical variables which were learning style preferences and English language achievement, and between learning style preferences and gender. It was found that contrary to the conclusions made by numerous earlier studies, there is no significant relationship between language learning styles and English language performance. In addition, it was also found that gender has no bearing in learning style preferences.